Analisis Performa Algoritme SPECK Pada Arduino Uno - Zuroul Mufarokah; Mochammad Hannats Hanafi Ichsan; Ari Kusyanti (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
SPECK algorithm is an algorithm that still has a family with lightweight block cipher algorithm. This algorithm was published by the National Security Agency (NSA) in June 2013. This algorithm is used to optimize in a software implementation. This algorithm has 10 block variants, namely block size 32 and key size 64 bits, up to block size 128 and key size 256 bits, selection of the three SPECK type variations following previous research that utilizes the AES algorithm to secure data where AES research has three variation based on the length of a key, AES-128, AES-192 and AES-256. In this study it can be concluded that between the results of encryption and decryption are valid with test vectors, SPECK block size 128 bits and key size 128 bits 1047.6 ms, SPECK block size 128 bits and key size 192 bit 1080.8 ms and SPECK block size 128 bits and key size 256 bits 1114.6 ms. Afterwards the results were put in Kruskal-Wallis and Post Hoc tests to be analyzed and concluded with each change While the results at the time of encryption and decryption of the three algorithms also have significant time differences.